Brucella Seropositivity and Associated Risk Factors in Pastoral Livestock System in Northeastern Ethiopia - Berhanu Sibhat; Haileeyesus Adamu; Teferi Benti; Getachew Tuli; Kassahun Asmare; Johanna F. Lindahl; Ulf Magnusson; Tesfaye Sisay Tessema (Veterinary Sciences)
Brucellosis is a common zoonotic disease affecting livestock and humans globally. The disease is endemic in Ethiopian livestock. This study was conducted to estimate Brucella seropositivity and identify its risk factors in livestock, and practices that may expose pastoralists to the disease. Data were collected from 2133 animals across 149 households (HHs) in Dubti and Amibara districts, Afar region, Ethiopia. Blood samples from livestock and household data were collected, and interviews were conducted on husbandry and dairy consumption practices. Sera were serially tested using the Rose Bengal test and indirect enzyme-linked immunosorbent assay. The overall seropositivity to anti-Brucella antibodies was 8% (95% CI, 6.6–9.2). The antibodies were found in 12.4%, 6.5%, 6%, and 3% of the goats, cattle, camels, and sheep, respectively. Among the HHs, 59.7% had at least one seropositive animal. A mixed-effects logistic regression analysis revealed species and the acquisition of new animals (in cattle and camels), and age and district (in sheep, goats, and cattle) as significant risk factors. Goats, cattle, and camels had significantly higher odds of Brucella seropositivity than sheep (p < 0.05). Seropositivity was significantly higher (p < 0.05) in adults than in young animals, in acquired than in homebred (cattle and camels), and in those with reproductive disorders than those without. Pastoralists lacked knowledge of brucellosis and its modes of transmission, while practices exposing humans and livestock to brucellosis were common. The findings underscore the need for public awareness campaigns and implementation of brucellosis control measures in pastoral systems.